Acid blue 25 adsorption on base treated Shorea dasyphylla sawdust: kinetic, isotherm, thermodynamic and spectroscopic analysis - Megat Hanafiah, Megat Ahmad Kamal; Wan Ngah, Wan Saime; Zolkafly, Shahira Hilwani; Lee, Ching Teong; Abdul Majid, Zafri Azran (Research Center for Eco-environmental Sciences,Chinese Academy of Sciences, 2012)
The potential of base treated Shorea dasyphylla (BTSD) sawdust for Acid Blue 25 (AB 25) adsorption was investigated in a batch adsorption process. Various physiochemical parameters such as pH, stirring rate, dosage, concentration, contact time and temperature were studied. The adsorbent was characterized with Fourier transform infrared spectrophotometer, scanning electron microscope and Brunauer, Emmett and Teller analysis. The optimum conditions for AB 25 adsorption were pH 2, stirring rate 500 r/min, adsorbent dosage 0.10 g and contact time 60 min. The pseudo second-order model showed the best conformity to the kinetic data. The equilibrium adsorption of AB 25 was described by Freundlich and Langmuir, with the latter found to agree well with the isotherm model. The maximum monolayer adsorption capacity of BTSD was 24.39 mg/g at 300 K, estimated from the Langmuir model. Thermodynamic parameters such as Gibbs free energy, enthalpy and entropy were determined. It was found that AB 25 adsorption was spontaneous and exothermic.